Comparative performance of various human papillomavirus assays available in Korea for detecting cervical intraepithelial neoplasia. Issue 1 (28th October 2021) - Ouh, Yung‐Taek; Park, Ji Jeong; Kang, Minjoo; Kim, Miseon; Song, Jae Yun; Shin, So Jin; Shim, Seung‐Hyuk; Yoo, Heon Jong; Lee, Maria; Lee, Sung‐Jong; Shin, Whan; Chong, Gun Oh.; et al.
Abstract: Aim: The aim of this study was to evaluate the clinical performance for detecting cervical intraepithelial neoplasia (CIN) 2 or higher lesions among available human papillomavirus infection (HPV) genotyping tests in Korea. Methods: Eligible patients visited 13 tertiary hospitals for colposcopic biopsy following cervical cytology and HPV genotyping test between January and December 2018. Baseline characteristics including age, body mass index (BMI), and parity were collected from 3798 patients. The performance of the Roche Cobas HPV 4800 was evaluated against other domestic HPV assays to detect CIN2 or higher. Results: A total of seven types of HPV genotyping tests were analyzed in the research institutes. A total of 1358 patients (35.8%) tested Anyplex II HPV 28 and 701 patients (18.5%) tested Cobas 4800 HPV. The overall sensitivity in the detection of CIN2 or higher was 41.5% (38.9–44.1) in patients positive for HPV 16/18. The Cobas test for HPV 16/18 was concordant with other assays evaluated for detection of CIN2 or higher and showed sensitivity of 46.6%, which was not significantly different from other assays. Although Anyplex II HPV28 (Seegene) showed slightly decreased sensitivity for detecting CIN2 or higher lesion with HPV 16/18 positive (39.8%, p  < 0.05) compared to Cobas 4800, in aspect of high‐risk HPV positive, Anyplex II HPV28 showed increased sensitivity (96.9%, p  < 0.05). Conclusion: The performance of the HPV genotype test that were commonly used in Korea was concordant with Cobas HPV test. Further studies are needed to evaluate the safety, efficiency, and cost‐effectiveness of the various commercially available domestic HPV assays.